Arthrogryposis Multiplex Congenita (AMC): Functional Improvement of a Seven-Year-Old Girl after 3 Years of Physical Medical Rehabilitation Intervention - Rahma Isma A.P; Naela Munawaroh (Faculty of Medicine, Universitas Airlangga, 2023)
Arthrogryposis multiplex congenita (AMC) is a genetic disease typified by non-progressive and multiple congenital limb contractures. The incidence of AMC is 1 in 3,000 live births, occurring in two or more areas of the body. The etiology of the syndrome is largely unknown and is multifactorial. The aim of this article is to report a patient diagnosed with arthrogryposis multiplex congenita who received physical medical rehabilitation intervention. We report a seven-year-old girl who frequently had symptoms of joint deformities, movement limitation, and walking difficulties. The patient's fingers and toes also had muscle hypoplasia and pterygium. She was diagnosed with arthrogryposis when she was born. Several surgical interventions had been performed. Since four years old the patient started the physical medical rehabilitation programs. Owing to the integrated orthopedic and medical rehabilitation therapy, it showed some improvements. The patient could walk by holding onto a bench and eat or drink by herself. The patient had obtained the daily living exercises using the correct compensation technique using modified tools. Physical medical rehabilitation programs can improve the functional condition of AMC patients. The goals of a physical medical rehabilitation treatment are to gain the walking ability and improve the ability to independently perform activities of daily living. Stretching exercises, ROM exercises, splints, modified tools, and orthopedic surgery are essential for arthrogryposis patients.